2013
DOI: 10.4236/health.2013.59183
|View full text |Cite
|
Sign up to set email alerts
|

Direct passive hemagglutination test for rapid quantification of plasma load of the <i>Human Immunodeficiency Virus</i>

Abstract: An inexpensive and rapid test for determining titers of Human Immunodeficiency Virus (HIV) in plasmas was developed. Washed sheep red blood cells were applied onto HIV positive plasmas, in V-bottomed microtiter plates, to complement the HIV antigens and antibodies present in plasmas. The setup was incubated for 30 minutes at 37˚C. Reciprocal of the highest dilution of each plasma which gave passive agglutination of the RBCs was read as its HIV titer. Mean HIV load of five samples, was ≥ 4096.00 ± 0.00 after on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…So, most people who claimed invention of cures for HIV/AIDS were not able to scientifically explain mechanisms of actions of the medicines. Development of the passive hemagglutination test for HIV [26] made in vitro test of antiretroviral effects of the MSAMS, possible [6].…”
Section: Discussionmentioning
confidence: 99%
“…So, most people who claimed invention of cures for HIV/AIDS were not able to scientifically explain mechanisms of actions of the medicines. Development of the passive hemagglutination test for HIV [26] made in vitro test of antiretroviral effects of the MSAMS, possible [6].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that when a sample tests negative for HIV with direct passive hemagglutination test, the test should be repeated, with the plasma diluted in HIV specific serum, in place of PBS, to ensure presence of HIV antibodies, before it can be concluded that such plasma is negative for the virus [25]. However, in this experiment, one out of the five plasma that tested positive to HIV antibodies by solid phase ELISA, was initially negative for the virus by direct passive hemagglutination test, but following incubation with AMS, it became HIV positive.…”
Section: Discussionmentioning
confidence: 99%
“…Another portion of each sample, not incubated with the AMS served as control. HIV titres of, supernatants of the plasma incubated with AMS once, plasma on which the incubation was repeated and the controls were assessed, by direct passive hemagglutination test [25]. Reciprocal of highest dilution of each plasma or plasma supernatant that gave complete passive agglutination of sheep red blood cells, was read as its HIV titre, on the condition that its next higher dilution tested positive to HIV antibodies, by the ELISA test.…”
Section: Methodsmentioning
confidence: 99%
“…There was a need for a simple, rapid and affordable in vitro test for HIV titer in specimens so that claims of antiretroviral effects of new medicines, herbs and minerals can be tested [4]. Those that give good results can then be used for clinical trials and outcome of the trials also scientific verified by testing plasma of treated patients for titer of the virus.…”
mentioning
confidence: 99%
“…So, it is necessary to test the next higher dilution to titer of each plasma, for HIV antibodies, to ensure that the antibodies remain so that it would be confirmed that what got diluted out is the antigen. Detection of HIV antibodies in plasma dilutions that test DPHA negative means that titer got by the DPHA test is titer of the antigen in the sample [4].…”
mentioning
confidence: 99%